Pengaruh Harga dan Pelayanan terhadap Keputusam Pembelian Konsumen pada Online Shop - Sudirman, Sudirman (Al-Buhuts, 2019)
This study aims to determine the effect of prices and services on consumer decisions in an online shop. Study on Islamic Economics and Business Faculty IAIN Sultan Amai Gorontalo Students. The sample selection method is done by using accidental sampling method. The number of samples chosen was 100 students. Data obtained through the distribution of questionnaires to the respondent. Data analysis was performed using multiple regression analysis tools. The type of data used is perimer data. The method of data collection is done by distributing questionnaires to those who are randomly responded. Data analysis was carried out using multiple regression analysis. The result of this study find out that the prices and services of online transactions together and partially positive and significant towards consumer decisions in conducting online purchase and purchase transactions at the Faculty of Economics and Islamic Business Sultan Amai Gorontalo IAIN, namely price variables with an exchange rate of 0.356 with a significant 0.034. Service variable with a coefficient of 2.423 with a significant value of 0.010. Then, together prices and services have a positive and significant effect on consumer decisions with the calculated F value = 5.930 significance 0.004 greater than F table = 3.590.